Recent Developments in Alpha-Glucosidase Inhibitors for Management of Type-2 Diabetes: An Update - Usman, Bashir; Sharma, Neha; Satija, Saurabh; Mehta, Meenu; Vyas, Manish; Khatik, Gopal L.; Khurana, Navneet; Hansbro, Philip M.; Williams, Kylie; Dua, Kamal (Current Pharmaceutical Design, 2019)
The incidence of diabetes has increased globally in recent years and figures of diabetic patients were estimated to rise up to 642 million by 2040. The disorder is accompanied with various complications if not managed at the early stages, and interlinked high mortality rate and morbidity with time. Different classes of drugs are available for the management of type 2 diabetes but were having certain limitations of their safety. Alphaglucosidase is a family of enzyme originated from the pancreas which plays a role in the anabolism of 80-90% of carbohydrate consumed into glucose. This glucose is absorbed into the blood and results in frank postprandial hyperglycemia and worsens the conditions of diabetic patients which precipitate complications. Inhibition of these enzymes helps to prevent postprandial hyperglycemia and the formation of glycated end products. Alphaglucosidase inhibitors are reported to be more important in adequate control of type 2, but marketed drugs have various side effects, such as poor patient compliance and also expensive. This proves the needs for other class of drugs with better efficacy, safety, patient compliance and economic. In this review, we have emphasized the recent advances in the field of new alpha-glucosidase inhibitors with improved safety and pharmacological profile.
Keywords: diabetes